Analisis Financial Distress pada PT. Air Asia Indonesia Tbk - Tuti Setiatin; Liska (Universitas Linggabuana PGRI Sukabumi, 2022)
This study aims to determine and analyze the level of bankruptcy using the Altman Z-Score method at PT. AirAsia Indonesia Tbk. Techniques The data collection is carried out using the Documentation Technique. The data analysis technique used is descriptive analysis with the Altman Z-Score method. This research was conducted from the period 2013-2021. The data used is the company's financial statements published through the official website of PT.AirAsia Indonesia Tbk. As for the dependent variable is the financial ratios contained in the Altman Z-Score method.The results of the study based on the bankruptcy criteria of the Altman Z-Score method showed that PT. AirAsia Indonesia Tbk for 9 years was in a period of bankruptcy in the 1-3 quarter of 2013, 2014-2018, the 1-3 quarter of 2019, 2020-2021. Only in the 4th quarter of 2013 and 2019 the company was in the gray area. PT. AirAsia Indonesia Tbk for 9 years, namely the period 2013-2022, has an average Z-Score of 0.28 which indicates that it is in a state of bankruptcy. In the Altman Z-Score method, the bankrupt area means PT. AirAsia Indonesia Tbk is in a state of financial difficulty while the gray area means PT. AirAsia Indonesia Tbk is in a vulnerable condition of bankruptcy. This has an impact on stock prices that continue to decline. So it is concluded that PT. AirAsia Indonesia Tbk is predicted to go bankrupt if it does not prepare the right steps to overcome bankruptcy.